How do you solve #x= -y-6# and #x=y-3# using substitution?

1 Answer
Mar 7, 2016

Answer:

Solution is #x=-9/2# and #y=-3/2#

Explanation:

To solve system of linear equation in two variables using substitution, one substitutes value of one variable from one equation in another equation.

In equations #x=−y−6# and #x=y−3#, let us substitute value of #x# (which is #y-3# into first equation which gives us

#y−3=−y−6# or by transposing similar terms #y+y=-6+3# or

#2y=-3# or #y=-3/2# and now putting this in #x=-3/2−3# or

#x=-9/2#

Hence solution is #x=-9/2# and #y=-3/2#